Living with floods – household perception and satellite observations in the Barotse floodplain, Zambia - Xueliang Cai; Haile, Alemseged Tamiru; Magidi, J.; Mapedza, Everisto D.; Nhamo, Luxon (Elsevier, 2017)
The Barotse Floodplain, a designated Ramsar site, is home to thousands of indigenous people along with an extensive wetland ecosystem and food production system. Increasingly it is also a popular tourist destination with its annual Kuomboka festival which celebrates the relocation of the king and the Lozi people to higher ground before the onset of the ood season. This paper presents an integrated approach which cross validates and combines the oodplain residents' perceptions about recent oods with information on ood inundation levels derived from satellite observations. Local residents' surveys were conducted to assess farmers’ perception on the ooding patterns and the impact on their livelihoods. Further, a series of ood inundation maps from 1989 to 2014 generated from remotely sensed Landsat imagery were used to assess the recent patterns of oods. Results show that the oodplain has a population of 33 thousand living in 10,849 small permeant or temporary buildings with a total cropland area of 4976 ha. The oodplain hydrologyand ooding patterns have changed, con rmed by both surveys and satellite image analysis, due to catchment development and changing climate. The average annual inundated areas have increased from about 316 thousand ha in 1989e1998 to 488 thousand ha in 2005 e2014. As a result the inundated cropland and houses increased from 9% to 6% in 1989 to 73% and 47% in 2014, respectively. The timing of the oods has also changed with both delaying and early onset happening more frequently. These changes cause increasing dif culties in ood forecast and preparation using indigenous knowledge, therefore creating greater damages to crops, livestock, and houses. Current oodplain management system is inadequate and new interventions are needed to help manage the oods at a systematic manner.